What do urban and rural hotel managers say about the future of hotels after COVID-19? The new meaning of safety experiences. (January 2022) - Robina-Ramírez, Rafael; Medina-Merodio, José Amelio; Estriegana, Rosa
Abstract: The pandemic crisis has caused a change in tourism trends that affect the way hotels are managed. In accordance with the United Nations (2020), hotels must guarantee safe experiences for customers by incorporating sustainability measures. Collaboration between health and tourism authorities and the tourism industry is key. To test this proposal among hotels in Spain, 3 online focus groups and 25 personal interviews with 36 urban and 28 rural hotels were held in order to define the indicators. The questionnaire was applied to a sample of 475 urban hotels out of 443 rural hotels. The conclusions were: 1.) While in urban areas the testing protocols, especially for workers, are followed by most hotels, in rural areas hotel managers do not consider it as a priority in daily activity due to the reduced contact they have. 2.) A change in trends in the sustainable management of both rural and urban hotels is justified. 3.) Urban and rural hotels are more likely to incorporate collaborative strategies with tourism and health authorities to reduce the negative impact of COVID-19. According to the estimates of the hotels, the implementation of these measures would help to start the recovery process of the hotel industry.